Perhitungan Energi Disosiasi Gugus Fungsi OH- dan PO43- Hidroksiapatit dengan Pemodelan Spektroskopi Inframerah Berbasis Particle Swarm Optimization (PSO) - Khusnul Yakin; Sidikrubadi Pramudito; Kiagus Dahlan (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Hydroxyapatite Ca10(PO4)6(OH)2 is a calcium phosphate compound having biocompatibility properties. FTIR (Fourier Transform Infrared Spectroscopy) was used to determine the characteristics of the hydroxyapatite group. Modeling the functional groups of hydroxyapatite can be used to obtain vibrational frequencies and spring constants. Analysis of energy release function is performed by calculating the dissociation energy. In this paper will be shown the results of theoretical modeling of hydroxyl and phosphate using spring models. Modeling the functional groups OH- obtained spring constant 524,4559 N/m and the absorption wave number 3497,5677 cm-1. Modelling functional groups PO43-obtained spring constant 612,2704 N/m and the wave number 1085,2559 cm-1 absorption. The constant and absorption wave numbers obtained are used to calculate the dissociation energy. OH- dissociation energy obtained by 566,5637 kJ/mol and the dissociation energy of PO43- is 567,6248 kJ/mol. Absorption wave numbers are obtained in accordance with experimental results on sometrik stretch modes, and the dissociation energy derived functional group is also close to the value of literature.